Editorial: Ecological restoration in drylands: toward land degradation neutrality - Deng, Jifeng; Xie, Shengbo; Gao, Guanglei; Gholami, Hamid (Frontiers in Environmental Science, 2024)
Land degradation neutrality (LDN) has been defined as “a state whereby the amount and quality of land resources necessary to support ecosystem functions and services remains stable or increases within specified temporal and spatial scales and ecosystems.” In practice, the application and success of LDN in drylands vary greatly depending on the targeted ecosystem services and the impacts of environmental conditions and various restoration methods on the efficacy and sustainability of restoration. In this editorial, we summarize the most viewed and downloaded articles contributing to the Research Topic “Ecological Restoration in Drylands: Toward Land Degradation Neutrality” of the journal Frontiers in Environmental Science.